Thermal performance evaluation in gas turbine aero engines accessory gearbox - Jafari, Soheil; Bouchareb, Ahmed; Nikolaidis, Theoklis (MDPI, 2020)
This paper presents a methodological approach for mathematical modelling and physics-based analysis of accessory gearbox (AGB) thermal behavior in gas turbine aero engines. The AGB structure, as one of the main sources of heat in gas turbine aero engines, is firstly described and its power losses will be divided into load-dependent and no-load dependent parts. Different mechanisms of heat generation are then identified and formulated to develop a toolbox for calculation of the churning, sliding friction, and rolling friction losses between contact surfaces of the AGB. The developed tool is also capable of calculating the heat loss mechanisms in different elements of the AGB, such as gears, bearings, and seals. The generated model is used to simulate and analyze the AGB thermal performance in the different flight phases in a typical flight mission, where the obtained results are validated against publicly available data. The analysis of the results confirms the effectiveness of the proposed method to estimate the heat loss values in the AGBs of gas turbine aero engines and to predict the thermal loads of the AGB in different flight phases. The developed tool enables the gas turbine thermal management system designers to deal with the generated heats effectively and in an optimal way.
Keywords: thermal management systems; accessory gearbox; gas turbine aero engines; heat loss mechanisms; thermal performance evaluation